Systematic Review Factors that Affect the Occurrence of Stunting - Rahmah Pujianti; Ummi Kalsum; Dwi Noerjoedianto (CV. Publikasi Indonesia, 2026)
Stunting in children aged 24 to 59 months is a health issue related to parenting patterns, social conditions, and family habits in meeting children's needs. This research aims to describe the factors related to the occurrence of stunting based on a review of six field research articles published between 2020 and 2025. Systematic review was conducted by searching articles in PubMed, Google Scholar, and Science Direct databases using keywords